MEMANTAPKAN UKHUWAH MENUJU MASYARAKAT MADANI - Asy'ari, M. (Hunafa: Jurnal Studia Islamika, 2005)
In Islam, brotherhood plays a great role. Even, Islam orders its adherents to build up brotherhood. Therefore, Islam orders its adherents to avoid  conflict  among them. If  two groups of Muslim  fight each other, Islam orders  the other group of  Muslim  to be mediator of the two disputing groups. It is the concept of Islam for  building up harmonious life among people that can lead to the intended civil society.